Resolving Impact Investment Disputes: When Doing Good Goes Bad - Deborah Burand (Washington University Journal of Law & Policy, 2015)
Impact investing, or investing with the goal of generating financial returns, is pursued within the context of advancing social goals. This Article describes the state of impact investing today and focuses on how to respond to impact investments that go awry by failing to meet investors’ financial expectations (rather than those that fail to meet investors’ social expectations). Burand then evaluates the appropriateness of using international arbitration as a dispute resolution mechanism for cross-border impact investing disputes, and suggests other resolution mechanisms that are capable of settling these disputes.
Keywords: impact investing; investing; dispute resolution